Left ventricular assist device therapy improves severe secondary mitral regurgitation without mitral valve repair. (14th October 2021) - Sharma, H; Yuan, M; Shakeel, I; Morley-Smith, A; Nadir, M A; Chue, C; Myerson, S G; Steeds, R P; Lim, S
Abstract: Background: Severe secondary mitral regurgitation (MR) worsens prognosis in patients with medically managed heart failure (HF). In patients treated by left ventricular assist device (LVAD), it is unclear whether severe MR should be corrected at time of LVAD implantation. Purpose: To evaluate impact of LVAD therapy on severe and non-severe secondary MR over 1 year. Methods: Retrospective single centre study of consecutive patients who underwent HeartMate (HM)2 or HM3 LVAD implantation between January 2011 and March 2020. Results: Of 155 patients, 20 were excluded due to LVAD exchange (n=10), mitral valve repair (n=1), or inaccessible pre-LVAD echocardiography (n=9). Based on multiparametric grading, 29/135 patients had severe secondary MR and 106/135 had non-severe secondary MR (including none). Severe MR patients were more often female [10/29 (34%) vs 11/106 (10%); p=0.002] but were of similar age (54±12 vs 55±9 years; p=0.624), size (27±5 vs 27±4 kg/m 2 ; p=1.0), with equivalent renal function (53±22 vs 55±20 ml/min/1.73m 2 ; p=0.641) and median pre-operative NT-proBNP [4076 (IQR 206–5438) vs 4914 (IQR 2706–7518) ng/L; p=0.488]. There were similar proportions of patients with ischaemic aetiology [16/29 (55%) vs 66/106 (62%); p=0.488) and those receiving HM2 [11/29 (38%) vs 32/106 (30%)] and HM3 [18/29 (62%) vs 74/106 (70%); p=0.575] LVAD. Echocardiography before LVAD implantation demonstrated similar left ventricular (LV) size (LV end-diastolic volume: 133±44 vs 118±50ml/m 2 ; p=0.145, end-systolic volume: 107±41 vs 96±59ml/m 2 ; p=0.348) and LV ejection fraction (17±9 vs 17±7%; p=1.0). Severe MR patients had significantly greater (p<0.001) MR by proximal isovolumetric surface area (0.93±0.27 vs 0.60±0.16cm), vena contracta (0.79±0.32 vs 0.57±0.18cm), regurgitant volume (47±25 vs 24±12ml), and fraction (54±15 vs 37±13%). Follow-up (f/u) echocardiography was performed at a median 222 days (range 356 days). Patients who received cardiac transplantation before f/u echocardiography were excluded. Relative severities of MR at f/u were: none = 12 (46%), mild = 8 (31%), moderate = 5 (19%), severe = 1 (4%) amongst patients with severe MR pre-LVAD, and none = 55 (58%), mild = 26 (27%), moderate = 13 (14%), severe = 1 (1%) amongst patients with non-severe MR pre-LVAD. At 1-year, after excluding all patients who underwent cardiac transplantation (severe MR n=4; non-severe MR n=2), rates of HF hospitalisation [5/25 (20%) vs 16/104 (15%); p=0.575] and all-cause mortality [2/25 (18%) vs 22/104 (21%); p=0.129)] were similar, irrespective of pre-LVAD MR severity. No patient who died during follow-up had severe MR prior to death. Conclusion: LVAD improves severe secondary MR in 96% of cases, resulting in 1-year rates of HF hospitalisation and mortality similar to patients without severe MR pre-LVAD. These data suggest mitral valve surgery at time of LVAD implantation is not warranted. Funding Acknowledgement: Type of funding sources: None.